Design of the information system of drug sales in pharmacies ita pharma - Ayudhia, Relina; Soebijono, Tony; Oktaviani, Oktaviani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Ita Farma Pharmacy is one of the pharmacies that are in District Kwanyar, These pharmacies provide pharmacy services regarding employment, namely the procurement of drugs, drug storage, preparation of drugs, compounding, distribution and delivery of pharmaceuticals and provide information to the public about the provisions of pharmacy. At this time Ika Farma Pharmacy is often in short supply of the drug because the pharmacy did not know the drug if supplies have been exhausted, it is only known if there is a buyer who wanted to buy drugs, then the process of recapitulation of sales per day is done every day by the cashier after the pharmacy closed and still done manually using a calculator. This causes the transaction recapitulation process takes a long time and possible errors in process recap. an information system that is intended to facilitate the sale of data storage sales transactions, inventory recording, and displaying information related to the sales reports are solutions to solve the problem. Conclusion The test results showed that the sales application can help the pharmacy to keep records inventory and daily sales reports that will be used as information about the development of Pharmacy.Keywords :  Information System, Sales, Pharmacies, Drug.